HUBUNGAN POWER OTOT TUNGKAI DAN POWER OTOT LENGAN DAN BAHU DENGAN AKURASI SMASH BOLA VOLI PADA TIM BOLA VOLI PUTRA SMA NEGERI 1 KERINCI KANAN - Azmi, Ulul; Slamet, Slamet; Alimandan, Alimandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on observations and observations made by the author in the field, and also based on information from coaches and athletes, that the men's volleyball branch of the Male Volleyball Team of SMA Negeri 1 Kerinci Kanan until now has not been able to show maximum achievement. One of the causes is smash. The purpose of this study was to determine the relationship between leg muscle power and arm and shoulder muscle power with volleyball smash accuracy in men's volleyball teams at SMA Negeri 1 Kerinci Right. Right. In this study the population that will be used is the men's volleyball team SMA Negeri 1 Kerinci Kanan consisting of 16 people. So the population in this study amounted to 16 people. The sample is a portion or representative of the population studied. The sample in this study was the men's volleyball team of SMA Negeri 1 Kerinci Kanan as many as 16 people. The instrument of this research is JUMP MD which aims to measure leg muscle explosive power, arm and shoulder muscle power test with medicine ball ball, and smash test. The data obtained were analyzed using simple and multiple correlations. From the results obtained, arm and shoulder muscle power has a relationship with Smash accuracy on the Men's Volleyball Team at SMA Negeri 1 Kerinci Kanan. There is a joint relationship between leg muscle power and arm and shoulder muscle power to the accuracy of the Smash on the Men's Volleyball Team at SMA Negeri 1 Kerinci Kanan. Key Words: Leg Muscle Power, Arm and Shoulder Muscle Power, Smash Accuracy